Performance of Prehospital Use of Chest Pain Risk Stratification Tools: The RESCUE Study. (19th May 2023) - Stopyra, Jason P.; Snavely, Anna C.; Ashburn, Nicklaus P.; O'Neill, James; Paradee, Brennan E.; Hehl, Brian; Vorrie, Jordan; Wells, Matthew; Nelson, R. Darrell; Hendley, Nella W.; Miller, Chadwick D.; Mahler, Simon A.
Abstract: Background: Emergency medical services (EMS) assesses millions of patients with chest pain each year. However, tools validated to risk stratify patients for acute coronary syndrome (ACS) and pulmonary embolism (PE) have not been translated to the prehospital setting. The objective of this study is to assess the prehospital performance of risk stratification scores for 30-day major adverse cardiac events (MACE) and PE. Methods: A prospective observational cohort study of patients ≥21 years of age with acute chest pain who were transported by EMS in two North Carolina (NC) counties was conducted from 18 April 2018–2 January 2019. In this convenience sample, paramedics completed HEAR (history, electrocardiogram, age, risk factor), ED Assessment of Chest Pain Score (EDACS), Revised Geneva Score (RGS), and pulmonary embolism rule-out criteria (PERC) assessments on each patient. MACE (all-cause death, myocardial infarction, and revascularization) and PE at 30 days were determined by hospital records and NC Death Index. The positive (+LR) and negative likelihood ratios (−LR) of the risk scores for 30-day MACE and PE were calculated. Results: During the study period, 82.1% (687/837) patients had all four risk score assessments. The cohort was 51.1% (351/687) female, 49.5% (340/687) African American, and had a mean age of 55.0 years (SD 16.0). At 30 days, MACE occurred in 7.4% (51/687), PE occurred in 0.9% (6/687), and the combined outcome occurred in 8.2% (56/687). The HEAR score had a − LR of 0.46 (95% CI 0.27–0.78) and + LR of 1.48 (95% CI 1.26–1.74) for 30-day MACE. EDACS had a − LR of 0.61 (95% CI 0.46–0.81) and + LR of 2.53 (95% CI 1.86–3.46) for 30-day MACE. The PERC score had a − LR of 0 (95% CI 0.0–1.4) and a + LR of 1.38 (95% CI 1.32–1.45) for 30-day PE. The RGS score had a − LR of 0 (95% CI 0.0–0.65) and a + LR of 2.36 (95% CI 2.16–2.57) for 30-day PE. The combination of a low-risk HEAR score and negative PERC evaluation had a − LR of 0.25 (95% CI 0.08–0.76) and a + LR of 1.21 (95% CI 1.21–1.30) for 30-day MACE or PE. Conclusion: The combination of a paramedic-obtained HEAR score and PERC evaluation performed best to exclude 30-day MACE and PE but was not sufficient for directing prehospital decision making.